Study of stress-induced anisotropy and effect of crack infill in oil and gas reservoirs - Collett, Olivia (Curtin University, 2015)
Seismic anisotropy, defined as the variation of seismic velocity with propagation direction, often affects seismic data significantly. In this thesis, theoretical models are developed for seismic anisotropy arising from the application of triaxial stress to dry rocks, and for the dependency of anisotropy parameters on the saturating fluid and seismic frequency. The theoretical results show good agreement with laboratory measurements, and are used to estimate compressional-wave anisotropy from shear-wave anisotropy obtained from borehole seismic data.